Clinical Utility of Anaerobic and Fungal Blood Cultures in the Pediatric Oncologic Population. Issue 5 (July 2020) - Kumar, Madan; Campos, Joseph; Hanisch, Benjamin
Abstract : Background: If there is a concern for sepsis in a pediatric patient an aerobic blood culture is obtained. A febrile or ill oncology patient will often be evaluated with aerobic, anaerobic, and fungal blood cultures. There is to our knowledge little evidence to confirm the added benefit of broadly obtaining these cultures. Methods: A retrospective analysis of blood cultures from patients in the oncology and hematopoietic stem cell transplant wards at Children's National Medical Center between January 2010 and April 2017. Positive anaerobic and fungal cultures were evaluated for corollary positive aerobic cultures from the same time frame (+/−24 h). Unique isolates were designated as those positive anaerobic and fungal cultures without positive aerobic cultures and evaluated with detailed chart review. Results: A total of 10, 950 cultures were evaluated during the study period: 6579 aerobic, 2391 anaerobic cultures, 1980 fungal. In total, 419 positive aerobic, 140 positive anaerobic, and 43 positive fungal cultures were reviewed. Among these, 22 unique anaerobic cultures and 21 unique fungal cultures met case criteria. Only 7 cultures of obligate anaerobes were observed: 4 Clostridial spp., 2 Propionobacterium acnes, and 1 Peptostreptococcus spp. Thirteen of 21 fungal isolates consisted of a single colony and were regarded as probable contaminants. Penicillium, Cladosporium, and dematiaceous molds were in greatest frequency. Potential risk factors for patients with breakthrough isolates were evaluated and described. Conclusions: There is little increased yield from the use fungal and anaerobic blood cultures in addition to aerobic blood cultures in the routine evaluation of pediatric oncology and bone marrow transplant patients. Fungal and anaerobic blood cultures and should be reserved for cases with high clinical suspicion.